ANALYSIS OF MACROECONOMIC VARIABLES TO STABILITY OF DINAR AND RUPIAH - Crebas, Lilla; Utami, Tiyas Puji; Furqoni, Habib Abda (International Conference of Business and Social Sciences, 2020)
Every country needs to balance their monetary policy in order to maintain the value of money. The current monetary system has no auto-balancing mechanism to prevent over supply of money which turns into hyperinflation. Dinar currency in the other hand, has the ability to maintain the supply in market due to limited resources to mint it. Previous studies did not compare the stability of fiat money and dinar altogether. This paper aims to identify each stability of fiat money and also dinar both in the short term and also in the long term. Vector Error Correction Model (VECM) is being used to estimate the effect of national trade, gross domestic product, and inflation to fiat currency and dinar. The result indicates that only inflation affects dinar currency and rupiah, while other variables did not affect significantly.